Penentuan Jalur Alternatif Menghindari Jalan Rawan Macet Di Kota Karawang Menggunakan Algoritma Djikstra - Ilham Hidayatullah; Betha Nurina Sari (Peneliti.net, 2022)
Congestion is one of the society problems, especially in big cities. Congestion occurs because the number of vehicles with width of roads that are not comparable. Therefore an appropriate alternative route selection method is needed to reduce congestion problems. This study aims to determine alternative pathways that are more effective and efficient so as to reduce congestion in certain road segments by determining the smallest weights from each road segmen with Djikstra Algorithm. This research produces several alternative routes that can be used to avoid certain road traffic jams, that people can choose different alternative routes according to their respective goals. The results of this study indicate that Djikstra algorithm can determine the optimal path as an appropriate alternative route to reduce congestion problems in the city of karawang.